The DQB1*03:02 Genotype and Treatment for Pain in People With and Without Multiple Sclerosis - Burkill, Sarah; Smith, Kelsi A.; Stridh, Pernilla; Kockum, Ingrid; Hillert, Jan; Lindahl, Hannes; Alfredsson, Lars; Olsson, Tomas; Piehl, Fredrik; Montgomery, Scott; Bahmanyar, Shahram (Frontiers in Neurology, 2020)
Murine models have demonstrated that the major histocompatibility complex (MHC) is associated with pain-like behavior in peripheral nerve injury, however the same association has not been shown when considering injury to the central nervous system (CNS), which more closely mimics the damage to the CNS experienced by MS patients. Previous research has indicated the DQB1*03:02 allele of the class II HLA genes as being associated with development of neuropathic pain in persons undergoing inguinal hernia surgery or with lumbar spinal disk herniation. Whether this HLA allele plays a part in susceptibility to pain, has not, as far as we are aware, been previously investigated. This study utilizes information on DQB1*03:02 alleles as part of the EIMS, GEMS, and IMSE studies in Sweden. It also uses register data for 3,877 MS patients, and 4,548 matched comparators without MS, to assess whether the DQB1*03:02 allele is associated with prescribed pain medication use, and whether associations with this genotype differ depending on MS status. Our results showed no association between the DQB1*03:02 genotype and pain medication in MS patients, with an adjusted odds ratio (OR) of 1.02, (95% CI 0.85-1.24). In contrast, there was a statistically significant association of low magnitude in individuals without MS (adjusted OR 1.18 (95% CI 1.03-1.35)), which provides support for HLA influence on susceptibility to pain in the general population. Additionally, the effect of zygocity was evident for the non-MS cohort, but not among MS patients, suggesting the DQB1*03:02 allele effect is modified by the presence of MS.